Germanium monotelluride-based solid solutions as whole-visible dielectric-metallic-transition material platforms for programmable metasurfaces. (15th May 2023) - Bi, Chaobin; Wang, Lei; Li, Ruifan; Zhao, Lin; Xue, Tianyu; Hu, Chaoquan; Wang, Xiaoyi; Chen, Qidai; Zheng, Weitao
Abstract: The development of next-generation programmable metasurfaces urgently requires phase change materials with dielectric-metallic transition (DMT-PCMs). Although DMT-PCMs in the infrared have been reported, DMT-PCMs in the visible spectrum are yet to be designed, limiting the nanophotonic applications of conventional programmable metasurfaces to the infrared band. Herein, we find that stoichiometric germanium monotelluride solid solutions, Ge1- x M x Te ( M = Sn, Sb, Pb, and Bi), have excellent DMT performance throughout the whole visible spectrum, and they can be used as versatile material platforms for fabricating programmable metasurfaces. As a proof-of-concept, the DMT performance of stoichiometric Ge0.9 Sn0.1 Te solid solution is significantly superior to that of commonly studied non-stoichiometric PCMs (e.g., Ge2 Sb2 Te5, Sb2 Te3 ). Through a combination of experiments and first-principle calculations, we demonstrate that the high DMT performance of Ge0.9 Sn0.1 Te derives from the unique bonding structure of the crystalline state with non-stoichiometric vacancy-free, high atomic number, and weak Sn-Te bonds, which is not present in conventional PCMs. Furthermore, using ultrashort-pulse lasers, we show that the crystalline Ge0.9 Sn0.1 Te can be arbitrarily written, erased, and modified at the subwavelength level. The resonance peaks and colors of the Ge0.9 Sn0.1 Te-based grating metasurface can be continuously modulated over the whole visible spectrum. These results suggest that the DMT material platforms can be used to fabricate programmable metasurfaces. Therefore, this work presents a coherent report on the physical origin, material design, and photonic devices of DMT in the visible spectrum, which may extend the applications of programmable metasurfaces from the infrared band to the visible spectrum and inspire more researches. Graphical abstract: Image, graphical abstract